Breaking the wave: The contested legitimation of an alien organizational form - Delmestri, Giuseppe; Wezel, Filippo Carlo (Journal of International Business Studies, 2011)
Organizational forms imbued with values of modernity – that is, rationality, efficiency and equity – diffuse rapidly around the world. Nonetheless, when sustained by beliefs, norms and regulations contrasting with those prevalent in the receiving country, their adoption may be delayed, and within-country legitimation may not proceed smoothly. We study the diffusion of multiplex cinemas – a form conceived in the US and attuned to the cinema-as-commerce logic – across Europe, where the cinema-as-art logic prevails. Our findings reveal that the cultural meanings embodied by multiplexes shaped the founding rates of this organizational form in three ways. First, countries with larger normative and regulative distance from the US retarded the adoption of the first multiplex. Second, camouflaged entries and, at increasing density, opposition from local interest groups were observed. Third, the embodiment of global cultural scripts of progress and modernity allowed multiplexes to overcome local opposition. The normative distance of the country from the US amplified the fluctuating dynamics of within-country legitimacy. A new specification of density-dependent legitimation is presented to model the cultural-cognitive legitimacy of rationalized but alien organizational forms.